Acute and convalescent samples from cohort study data for serological assays, colored by whether they are predicted as infections using Model 9. - Marco Hamins-Puértolas (15238661) (2025)
Green points represent no predicted infection while samples classified as an infection are split into two groups, those with no positive serological interpretations (RT-PCR, HAI, and EIA) in red while those with at least one positive serological interpretation are blue. a) Geometric mean titers of a haemagglutination inhibition assay (GM HAI) for all four serotypes of dengue virus. b) Immunoglobulin G (IgG) c) Immunoglobulin M (IgM) d) Ratio of IgM to IgG at both acute and convalescent serum samples. (TIF)